Fading of Affect Associated with Negative Child‐Related Memories Varies by Parental Child Abuse Potential. Issue 6 (10th November 2016) - Skowronski, John J.; Crouch, Julie L.; Coley, Sarah L.; Sasson, Sapir; Wagner, Michael F.; Rutledge, Ericka; Cote, Kreila; Miksys, Christie; Milner, Joel S.
Summary: Positive memories tend to hold their affective intensity across time better than negative memories, a phenomenon referred to as the fading affect bias (FAB). An initial study explored this bias in the context of parents' affective responses to memories involving their children. Specifically, parents (N = 90 for Study 1) were asked to recall three positive events and three negative events involving their children. Next, parents rated how positively or negatively they felt when each event occurred and at recall. Results revealed that parents at high risk of physical child abuse showed a smaller FAB than low‐risk parents. The smaller FAB effect observed among high‐risk parents occurred largely because affect associated with negative child‐related events faded minimally over time. This risk moderation effect did not emerge in a second study in which parents (N = 90 for Study 2) recalled general events that were not limited to events involving children. Copyright © 2016 John Wiley & Sons, Ltd.